Hubungan Tingkat Pengetahuan Ibu Terhadap Pemberian Imunisasi DPT Di Puskesmas Labuhan Deli Kecamatan Labuhan Deli Kabupaten Deli Serdang Tahun 2023 - Sonia Novita Sari; Rayani Nainggolan; Nopa Isabela Napitupulu; Yesica Geovany Sianipar; Friza Novita Sari Situmorang; Ariska Fauzianty (Jurnal Medika Nusantara, 2023)
Immunization is an effort to provide immunity to infants and children by injecting vaccines into the body so that the body makes a substance to prevent certain diseases. This study aims to determine the relationship between the mother's level of knowledge and the provision of DPT immunization at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency. This research is an analytical quantitative research using a cross sectional design. The population in this study were mothers who had babies aged 6-12 months, namely 42 respondents at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency in 2023. The sampling technique was total sampling. Data collection was analyzed by chi-square test. The results of this study indicate that there is a significant relationship between the mother's knowledge level and the administration of DPT immunization at the Labuhan Deli Health Center, Labuhan Deli District, Deli Serdang Regency, with a p value <0.05 (0.009).